Assessment of dietary intake: technology, accuracy, and measurement error - Whitton, Clare (Curtin University, 2023)
The aim of this thesis was to evaluate and elucidate the underlying drivers of accuracy and error in the estimation of dietary intake among adults, using self-reported methods. A multi-pronged approach was used to address the multiple components involved in the collection of accurate dietary intake data. Four studies were conducted, including the evaluation of leading dietary assessment methods, featuring web and mobile applications, and the exploration of demographic, psychosocial, and cognitive correlates of accuracy and error.